Enhancing pyrolysis oil yield and quality via low-temperature catalytic pyrolysis of pet waste over activated carbon derived from euxideroxylon zwageri - Ahmad Yani; Widya Wijayanti; Mega Nur Sasongko; Slamet Wahyudi; Dwi Irawan (Mechanical Engineering for Society and Industry, 2026)
This study evaluates the low-temperature pyrolysis of post-consumer polyethylene terephthalate (PET) from room temperature to 350 °C using biomass-derived activated carbon from Euxideroxylon zwageri (EZAC) as a renewable catalyst/adsorbent. PET–EZAC blends (100:0, 95:5, 90:10, 85:15, and 80:20; total feed 500 g) were processed in a fixed-bed reactor under an inert atmosphere. EZAC significantly shifted product distribution and exhibited an optimum at PET:EZAC = 90:10 (w/w), which produced the maximum oil yield of 543 mL (404 g; 80.8 wt%) and exceeded the oil yield from non-catalytic PET pyrolysis. Under this optimum condition, fuel-relevant properties improved, yielding an research octane number (RON) of 97 and a higher heating value (HHV) of 47.88 MJ/kg; the flash point and kinematic viscosity decreased to 13 °C and 2.384 cSt, respectively, while density remained nearly constant (0.772 g/mL). GC–MS results showed the most gasoline-like composition at PET:EZAC = 90:10, dominated by the C7–C10 fraction (62.95%) with a balanced hydrocarbon-class distribution (Alkanes 64.64%, Olefin 27.61%, and Aromatics 7.75%). MQ sensor-based gas profiles further suggested that EZAC accelerated the onset of H₂ and CH₄ formation, with peak sensor responses of 745 ppm for H₂ and 871 ppm for CH₄ at 20% EZAC. Overall, EZAC is a promising renewable material for steering secondary reactions during low-temperature PET pyrolysis, thereby improving both oil yield and oil quality.